EVALUASI PENGGUNAAN RUANG LAUT MENGGUNAKAN VISUALISASI 3D (STUDI KASUS : KECAMATAN CAMPLONG, KABUPATEN SAMPANG) - Muhammad Firdaus; Agung Budi Cahyono (Kokoh, 2021)
Based on the final drafting document of RZWP-3-K (Zoning Plan for Coastal Areas and Small Islands) in East Java, Sampang Regency has various utilization of marine space, including: traditional fishing areas, fish farming, FSO (Floating Storage Offloading), The Fuel Oil Terminal (TTU-BBM), the sand sea mining location permit, the coastal tourism area, the military training area, the oil and gas pipeline that is operated by PT.Santos Ltd and so on. This results in the utilization of coastal areas and diverse (multi-use) marine space located on the water surface, water column, the subsoil of the bed in one vertical plane of a marine parcel. Then there is a need for marine space utilization allocation planning (RZWP3K). The application of the concept of marine cadastre is a solution in determining the limits of allocation and the type of utilization of marine space so as not to cause future conflicts. However, in the use of marine space there is still a mismatch with the marine space allocation plan that has been made by the East Java Marine and Fisheries Service and in its planning it still uses maps with 2D visualization which basically cannot visualize the condition vertically the condition of a marine parcel is overlapping or not, so 3D visualization is needed.Keywords: 3D Visualization, Marine Cadastre, Marine Space, RZWP3K, Utilization Suitability of Sea Space